The Impact of Contribution Density, Size, Idle Contributions, and Pension Funds’ Performance - Ibrahim, Majeed Ajibola; Rabiu, Sherifdeen Adebola; Agbeyinka, Ibrahim Yinka (Ilomata International Journal of Tax and Accounting, 2024)
Purpose: Pension funds administrators (PFAs) are currently seen as reliable catalyst for steady economic growth and development. The need to ensure management of pension funds in the best possible ways or most effective manner was borne out of the need to ensure that they yield better returns on investment. This study attempts to offer answers to three issues based on evidence from Nigeria. We attempt to find (a) to what extent has the density of pension contribution influence the investment performance of PFAs? (b) to what extent has idle contribution affect the investment performance of PFAs? And (c) to what extent does the pension contribution size induce the investment performance of PFAs? Method: We applied the generalized least square (GLS) regression based on PFAs performance between 2014 and 2023, evaluate the connection between four financial assets that the PFAs in Nigeria invest in and the investment returns. Results: We find that density of the contribution, idle contribution, contribution size, total pension fund assets and leverage are critical in determining the investment performance. A positive coefficient was reported for the adopted regressors for contribution density. This implied that the selected PFAs could improve their performance considerably if credence is given to their contribution density because contribution density is major key driver of a PFAs performance. Novelty: We recommend measures that would boost the sustainability of pension funds, securing better retirement outcomes for contributors and strengthening Nigeria’s financial ecosystem.